EVALUASI PELAKSANAAN PENDIDIKAN DAN PELATIHAN KOMPETENSI SUMBER DAYA APARATUR (STUDI DI BADAN KEPEGAWAIAN DAERAH KOTA MAGELANG) - ., Mulyaningsih (Jurnal Administrative Reform, 2016)
This paper analyzes the evaluation of the implementation of education and training (training) the competence of government personnel resources Badan Kepegawaian Daerah (BKD) Kota Magelang. This study used a qualitative method with descriptive approach. The purpose of this study was to evaluate aspects of competency training. The training components that are evaluated are training curriculum, length of training, training methods, trainers, training participants, training infrastructure and training committee organized by BKD Kota Magelang. This study shows that the implementation of competency training has been going well and in accordance with the specified criteria even though there are still some obstacles.